Modelling giant red shrimp larval dispersal in the Sardinian seas: density and connectivity scenarios. (13th January 2017) - Palmas, Francesco; Olita, Antonio; Addis, Piero; Sorgente, Roberto; Sabatini, Andrea
Abstract: The connectivity and three‐dimensional (3D) dispersion of the larvae of giant red shrimp, potentially released from known spawning areas along the Sardinia slope in the western Mediterranean Sea, were assessed using Lagrangian simulations forced by a 3D submesoscale permitting a regional ocean model. Biophysical simulations using the hydrodynamic conditions of the year 2012 were run to track propagules released from known spawning areas during the spawning period (May to September). Passive transport (PT) and vertical migration (VM) scenarios were tested, each with two possible pelagic larval durations (PLDs) of 21 or 42 days. Dispersion of propagules in the PT and VM scenarios differed in terms of travelled distance, export out of the domain (larger for VM), and depth distribution (shallower and bimodal for VM due to the larger variability of encountered currents). Connectivity patterns were investigated among eight release areas, and four predetermined Eco‐Regions, and results showed strong connectivity among the North‐Western (NW), Western (W), and Southern (S) regions of Sardinia, whereas the Eastern region was more segregated. Differences in connectivity patterns among scenarios were related mainly to the tendency of greater retention of propagules in the release area for the PT scenarios. This finding, together with existing hypotheses of vertical migration likely occurring during first egg‐larval phases, suggest that the VM scenarios are the most probable of the two hypotheses tested. Strong connectivity between the W and S sides of Sardinia and the relative isolation of the E side could have significant implications for the protection of this important resource.